Association between intimate partner violence during pregnancy and maternal pregnancy complications among recently delivered women in Bangladesh. Issue 3 (7th February 2018) - Ferdos, Jannatul; Rahman, Md. Mosfequr; Jesmin, Syeda S.; Rahman, Md. Aminur; Sasagawa, Toshiyuki
Abstract : Intimate partner violence (IPV), an actual or threatened physical, sexual, or psychological abuse by a current or former partner or spouse, is a common global public health issue. Understanding both the prevalence of IPV during pregnancy and its potential impact on the health of pregnant women is important for the development and implementation of interventions to prevent maternal morbidity and mortality. The purpose of this study was to explore the association between maternal experiences of IPV during pregnancy and pregnancy complications. A health‐facility‐based cross‐sectional study was conducted from July 2015 to April 2016 among 400 randomly selected women who were admitted to the postnatal wards of Rajshahi Medical College Hospital for delivery. Data were collected through face‐to‐face interviews using a structured questionnaire. Multivariable logistic regressions were performed to assess relationships between variables of interest after controlling for potential confounders. Results indicated that 39.0% of women reported physical IPV and 26.3% of women reported sexual IPV during pregnancy. Additionally, 69.5% of women experienced medical complications (MCs); of this group, 44.3% experienced obstetric complications (OCs) and 79.3% experienced any pregnancy complication (AC) during their last pregnancy. The experience of physical IPV during pregnancy was significantly associated with the experience of MCs (adjusted odds ratio (AOR): 2.05, 95% confidence interval (CI): 1.15–4.01), OCs (AOR: 4.23, 95% CI: 2.01–7.12) and AC (AOR: 5.26, 95% CI: 2.98–10.52). Women who experienced sexual IPV during pregnancy were also at increased risk of suffering from any MC, any OC, and AC. Maternal experience of IPV during pregnancy is positively associated with pregnancy complications. Preventing IPV directed at pregnant women might reduce maternal morbidity and mortality in Bangladesh.